A P2P framework for modular disjunctive knowledge bases with negation and constraints and its applications to the semantic web. (5th May 2022) - Analyti, Anastasia
The paper presents present a P2P framework based on asynchronous messaging for collaborative reasoning over modular disjunctive knowledge bases with weak negation, strong negation, and constraints. In particular, the paper presents algorithms running upon receival from a knowledge base of a corresponding Ask_pred, Tell_pred, Ask_KB, or Tell_KB message, which are needed for query answering. In particular, these messages collect in the knowledge base that received the query which is the corresponding part of the modular knowledge base that is needed for query answering. This process is done in polynomial time with respect to the size of the modular knowledge base. The paper presents several applications of the proposed theory, including restricted modular ERDF ontologies, SPARQL 1.1 seen as a rule language, the maximal weak model semantics, the minimal weak model semantics, multi-context reasoning, the contextually closed semantics, and taxonomy-based sources connected by articulations. Several complexity results are provided.